Perkembangan Keuangan Syariah di Indonesia: Sebuah Tinjauan Deskriptif - Rahmarisa, Faty; Yudha, Tri Kartika; Azim, Fauzan; Pasaribu, Donald Frensius (Universitas Islam Sumatera Utara, 2024)
Since the early 1990s, Islamic finance in Indonesia has witnessed remarkable expansion, marked by advancements in the banking sector, non-bank financial institutions, and capital markets. This article seeks to elucidate the evolution of Islamic finance in Indonesia, encompassing Islamic banking, Islamic insurance, Islamic financing entities, and the Islamic capital market. Furthermore, it addresses the challenges and opportunities that the Islamic finance sector encounters in Indonesia. The findings of this research indicate that Islamic finance possesses significant potential to emerge as a fundamental component of the national financial system.